Model Panel Surya Cerdas Dengan Sensor Pelacak Cahaya Matahari Otomatis Berbasis Mikrokontroler - Harjunowibowo, Dewanto (BERKALA FISIKA, 2010)
This research aims to create a model of intelligent solar panels are able to follow the movement direction of the sun as an energy source based on microcontroller AVR ATMEGA. This study uses ATMEGA AVR microcontroller 16bit with injection of fuzzy logic programs. The system also created using 4 (four) sensors LDR and 5 (five) photodiode sensor. Integration of fuzzy logic, AVR ATMEGA and sensors capable of providing optimal results into a dynamic model of the solar panels that automatically and can be applied on a large scale. The results of this study is a prototype solar panel that is able to follow the movement direction of the sun based on microcontroller AVR ATMEGA 16. The solar panels model is capable of putting solar panel surface perpendicular to the direction of sunlight intensity can be detected along the sensor. Keywords: smart panel, microcontroller, fuzzy logic, sensor